Crime Rates and Access to Banking Services: An International Comparison - Keery, Anne (Université d'Ottawa | University of Ottawa, 2008)
The question motivating this paper is, "Does increasing access to banking reduce the occurrence of crime?" The answer is a resounding "yes!" To answer the question, a series of sandard OLS regressions are performed based on the model used by Soares (2004)